(untitled) (Communications in Computational Physics, 2018)
In this paper we present a parallelization strategy on distributed memory systems for the Fast Kinetic Scheme — a semi-Lagrangian scheme developed in [J. Comput. Phys., Vol. 255, 2013, pp 680-698] for solving kinetic equations. The original algorithm was proposed for the BGK approximation of the collision kernel. In this work we deal with its extension to the full Boltzmann equation in six dimensions, where the collision operator is resolved by means of fast spectral method. We present close to ideal scalability of the proposed algorithm on tera- and peta-scale systems.